2022
DOI: 10.1007/s40121-022-00678-w
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes (PROs) in HIV Infection: Points to Consider and Challenges

Abstract: Introduction:The aim of this study was to reach consensus on the use of PROs (patientreported outcome measures) in people living with HIV (PLHIV).Methods: A scientific committee of professionals with experience in PROMs methodology issued recommendations and defined the points to support by evidence. A systematic review of the literature identified the coverage, utility, and psychometric properties of PROMs used in PLHIV. A Delphi survey was launched to measure the degree of agreement with the recommendations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Only about a quarter of these could be considered standard of care in their clinical environments, suggesting that routine collection of PRO data is not well-integrated across HIV care settings [144,145]. Nevertheless, these initiatives spanned 19 countries, with half led in North America.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only about a quarter of these could be considered standard of care in their clinical environments, suggesting that routine collection of PRO data is not well-integrated across HIV care settings [144,145]. Nevertheless, these initiatives spanned 19 countries, with half led in North America.…”
Section: Discussionmentioning
confidence: 99%
“…This rapid scoping review found 60 published initiatives (2007–2022) that clinically administered PROMs to inform the individual management of patients with HIV. Only about a quarter of these could be considered standard of care in their clinical environments, suggesting that routine collection of PRO data is not well‐integrated across HIV care settings [144, 145]. Nevertheless, these initiatives spanned 19 countries, with half led in North America.…”
Section: Discussionmentioning
confidence: 99%
“…Persons living with HIV valued the use of PROMS (even without validation) viewing them as a contribution and useful for individualized care, whereas health professionals expressed negative impressions of PROM use citing an excessive number of PROMs and lack of time to administer. 44 These impressions may extend to community settings with limited resources, space, and personnel. Ultimately, having buy-in from all stakeholders will be critical for SF-HDQ uptake and use in community settings.…”
Section: Discussionmentioning
confidence: 99%